2021
DOI: 10.1016/j.htct.2020.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Maximum Blood Ordering for Surgery (MSBOS) in elective general surgery, neurosurgery and orthopedic surgery at the Poursina Hospital in Rasht, Iran, 2017

Abstract: Introduction Blood is a valuable life resource that depends on the donation of blood by the community. As a result, it is crucial that the manner in which this expensive resource is used be correct and reasonable. Objective The purpose of this study was to investigate the Maximum Blood Ordering for Surgery (MSBOS) in general, orthopedic and neurosurgical elective surgeries at the Poursina Hospital in Rasht in 2017. Methods According to the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…The inclusion criteria of the documents that we deem fit for reviewing articles are research journals and newspaper articles from good sources, reported in English, relevant and reliable, and discussing the ethics of elective orthopaedic surgery during the pandemic [ 14 , 15 ]. Studies are excluded if they lack reliable, inaccessible, and expensive references.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria of the documents that we deem fit for reviewing articles are research journals and newspaper articles from good sources, reported in English, relevant and reliable, and discussing the ethics of elective orthopaedic surgery during the pandemic [ 14 , 15 ]. Studies are excluded if they lack reliable, inaccessible, and expensive references.…”
Section: Methodsmentioning
confidence: 99%
“…Although MSBOS has proven to be an effective tool for reducing unnecessary cross-matching, it is affected by many factors 14,29,35 . Every single patient undergoing surgery has different risks for bleeding and transfusion.…”
Section: Efficacy Of Blood Utilization In Non-covid Patients During T...mentioning
confidence: 99%
“…Tabela 5-Análise do índice de pacientes transfundidos nos procedimentos cirúrgicos realizados no Hospital Ophir Loyola. Estudos sugerem a realização de compatibilização de pelo menos dois concentrados de hemácias (Ural et al, 2016;Moghaddamahmadi et al, 2021), de fato, notou-se, que a maioria dos procedimentos realizados no hospital necessita de cerca de dois concentrados de hemácias (Figura 5). Acredita-se, ainda, que a perda média estimada de sangue na maioria dos procedimentos cirúrgicos seja de 100-600 mL (Sharingcarinkul & Chuasuwan, 2018), o que corresponde em média a um volume comportado normalmente por um a dois concentrados de hemácias.…”
Section: Patologiaunclassified